Evaluation of the Opinions of the People Concerning the Forensic Medical Services in Samsun - Süer, Cenk; Turla, Ahmet; Aydın, Berna (The Bulletin of Legal Medicine, 2015)
Objective: Forensic medicine services, directly contributes to justice to be served, strongly effects solutions for judicial problems. Aware community about the services provided from forensic medicine, knowledge resources, independence or confidence of the evaluation and provide recommendation that based on obtained data.Materials and Methods: In total, representation of all segments of society living in the city centre of Samsun 5 different groups acording to their jobs were (Students, workers, civil servants, self-employed and housewives) included in the study. 201 civil servant, 207 workers, 205 self-employed, 204 students and 200 housewives. In total 1017 participants were included in the study. The data obtained from the cases noted, investigated and analysed by using the statistical programme. (SPSS 16.0)Results: The study was based on 1017 people. 471 (46.3%) men and 546 (53.7%) women, the mean age was 34,6 ±11,8 (18-65). 887 (87.2%) of the participants believed that television were the most common source for gathering information about forensic medicine. Out of all the services Forensic Medicine department provides, people believes that autopsy is the most common and well-known service. However, the most common opinion that people do not trust the Forensic Medicine expert witness is that work being done under pressure and also making decisions impartially. 747 (73,5%) of the participants were stated that they would not be against having autopsy process to them or their relatives.Conclusion: Public society’s interest increases to institutions and organisation that provides Forensic Medicine services every day. The major tasks undertaken and followed up...
Keywords: forensic medicine; awareness; reliability